A Coadditive Strategy for Blocking Ionic Mobility in Methylammonium‐Free Perovskite Solar Cells and High‐Stability Achievement. Issue 5 (26th March 2021) - Zheng, Daming; Zhu, Tao; Pauporté, Thierry
Abstract : Herein, the synthesis of methylammonium‐free and bromide‐free Cs x FA1− x PbI3 (FA for formamidinium) perovskite (PVK) photovoltaic layers with intrinsic outstanding properties in terms of crystallinity, defect waiving/passivation, and ionic mobility blocking by using a coadditives approach is described. It consists in mixing two chloride additives in the PVK precursor solution: potassium chloride (KCl) and ammonium chloride (NH4 Cl). KCl favors the lead iodide (PbI2 ) precursor solubilization and results in a purer PVK phase. NH4 Cl allows the control of the crystallization growth speed, leading to the formation of large crystal grains and well‐crystallized layers. By the glow‐discharge optical emission spectroscopy (GD‐OES) technique, it is directly visualized that potassium incorporated in the whole film blocks the iodide mobility by defect passivation. Also, the reduction (or suppression) of iodide mobility and the reduction (or suppression) of the J–V curve hysteresis is clearly correlated. It is found that blocking the ionic mobility is insufficient to fully stabilize the halide perovskite material which also requires the crystallization monitoring carried out in parallel by the second additive. It resulted in Cs0.1 FA0.9 PbI3 cells with a stabilized power conversion efficiency (PCE) of 20.02% and with superior stability. Abstract : A coadditive strategy using two chloride compounds in the precursor solution is elaborated to prepare methylammonium‐free Cs0.1 MA0.9 PbI3 layers with outstanding morphological, structural, electrical, and optical properties. It results in robust devices which are hysteresis‐free and deliver a stabilized 20.02% power conversion efficiency.